Pengaruh Customer Relationship Management, Service Quality, Dan Brand Image Terhadap Customer Loyalty Dengan Customer Satisfaction Sebagai Variabel Intervening : Studi Pada Pengguna Aplikasi MC`Donalds Di Jakarta - Irham Maulana; Osly Usman; Nadya Fadillah Fidhyallah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the influence of Customer Relationship Management, Service Quality, and Brand Image on Customer Loyalty, with Customer Satisfaction as an Intervening Variable: A Study of McDonald's App Users in Jakarta. This study provides a theoretical contribution to the development of marketing and consumer behavior studies, particularly in the context of app-based digital services in the fast food industry. The conclusion that Customer Relationship Management, Service Quality, and Brand Image have a positive and significant effect on Customer Satisfaction, and that Customer Satisfaction has a positive and significant effect on Customer Loyalty, supports and strengthens the results of previous studies in the realm of relationship marketing and customer satisfaction. Specifically, this study expands the application of these concepts to the McDonald's digital app environment. Thus, this study can serve as a theoretical reference for further research examining customer satisfaction and loyalty in the context of app-based digital services.